Prince Sakolworanakorn Worawan and Thai Municipality - chaiching, ืnattapoll (King Prajadhipok’s Institute Journal, 2020)
This article is a study of the local government development in Thailand through the role of Prince Sakonwanakorn Worawan, as he played an important role in driving Thai municipalities under absolute monarchy and democracy, including the roles of civil servants, law committees, political consultants, parliamentary candidates, labor leaders, and academics. Which his hoped that the municipality be the foundation of democracy and social justice for his country. In addition, this article proposes that the origin of Thai local government was not the Traditional Thai State but also it was born in the modern state. e had played an important role in driving this success.